Rhizobacterial consortium mediated aroma and yield enhancement in basmati and non-basmati rice ( Oryza sativa L.) - Dhondge, Harshal V.; Pable, Anupama A.; Barvkar, Vitthal T.; Dastager, Syed G.; Nadaf, Altafhusain B. (Journal of Biotechnology, 2021)
Basmati and non-basmati rice varieties are commercially important. Aromatic rice varieties are low yielding and recently depletion in aroma is observed due to the shift towards modern agriculture. Therefore, it is necessary to restore the aroma and increase the yield through sustainable agriculture. The use of microbial bioinoculants is one of the promising ways to achieve these targets. With these objectives, rhizospheric bacterial strains Enterobacter hormaechei (AM122) and Lysinibacillus xylanilyticus (DB25) having the property of synthesizing 2acetyl-1-pyrroline (2AP) were isolated from the rhizosphere of two aromatic rice varieties, Ambemohar-157 and Dehradun Basmati respectively and their effect on plant growth, aroma and yield enhancement under mono-inoculation and consortium conditions was analyzed. The bacterial inoculum in consortium resulted in significant improvement in vegetative growth, yield and 2AP content over mono inoculation and control. The study highlights the potential of E. hormaechei and L. xylanilyticus in plant growth, yield and aroma enhancement in basmati and non-basmati rice varieties. These strains can be taken up further for developing a commercial bioformulation.
Keywords: 2-Acetyl-1-pyrroline; Basmati rice; Non-basmati rice; plant growth promotion; Rhizosphere; yield

Genome sequencing and protein modeling unraveled the 2AP biosynthesis in Bacillus cereus DB25 - Dhondge, Harshal V.; Barvkar, Vitthal T.; Dastager, Syed G.; Dharne, Mahesh S.; Rajput, Vinay; Pable, Anupama A.; Henry, Robert J.; Nadaf, Altafhusain B. (International Journal of Food Microbiology, 2024)
2-Acetyl-1-pyrroline (2AP) is an important and major flavor aroma compound responsible for the fragrance of basmati rice, cheese, wine, and several other food products. Biosynthesis of 2AP in aromatic rice and a few other plant species is associated with a recessive Betaine aldehyde dehydrogenase 2 (BADH2) gene. However, the literature is scant on the relationship between the functional BADH2 gene and 2AP biosynthesis in prokaryotic systems. Therefore, in the present study, we aimed to explore the functionality of the BADH2 gene for 2AP biosynthesis in 2AP synthesizing rice rhizobacterial isolate Bacillus cereus DB25 isolated from the rhizosphere of basmati rice (Oryza sativa L.). Full-length BcBADH2 sequence was obtained through whole genome sequencing (WGS) and further confirmed through traditional PCR and Sanger sequencing. Then the functionality of the BcBADH2 gene was evaluated in-silico through bioinformatics analysis and protein docking studies and further experimentally validated through enzyme assay. The sequencing and bioinformatics analysis results revealed a full-length 1485 bp BcBADH2 coding sequence without any deletion or premature stop codons. Full-length BcBADH2 was found to encode a fully functional protein of 54.08 kDa with pI of 5.22 and showed the presence of the conserved amino acids responsible for enzyme activity. The docking studies confirmed a good affinity between the protein and its substrate whereas the presence of BcBADH2 enzyme activity confirmed the functionality of BADH2 enzyme in B. cereus DB25. In conclusion, the findings of the present study suggest that B. cereus DB25 is able to synthesize 2AP despite a functional BADH2 gene and there may be a different molecular mechanism responsible for 2AP biosynthesis in bacterial systems, unlike that found in aromatic rice and other eukaryotic plant species.
Keywords: 2-Acetyl-1-pyrroline; Basmati rice flavor; Betaine aldehyde dehydrogenase 2; Protein-ligand docking; Rhizobacteria; Whole-genome sequence